Adolescents with attention deficit hyperactivity disorder - taking a sexual history. (24th May 2012) - Onugha, NN; Finlay, F
Abstract : Background: Adolescents are having sex and adolescents with Attention Deficit Hyperactivity Disorder (ADHD) are no exception. A number of studies have found an increase in high-risk sexual behaviour in young people with ADHD. Sexual history taking is the first step toward providing reproductive, contraceptive and sexually transmitted disease (STD) counselling. Methods: A retrospective review of the clinical notes of fifty adolescent patients aged 12-18 years with a formal diagnosis of ADHD was carried out by two researchers. Consultations with both paediatricians and ADHD nurse specialists were reviewed from the first time the young person was seen over the age of 12 years until the last consultation, with a view to establishing whether a sexual history was taken on any occasion. Results: None of the healthcare professionals took a sexual history from any of the adolescents on any occasion despite multiple clinic attendances. Conclusion: Adolescents with ADHD are more likely to engage in high-risk sexual behaviour and it is therefore the job of paediatricians and specialist nurses to educate patients regarding their increased risk, re-evaluation of lifestyle behaviours, and preventative measures. The World Health Organisation describes sexual health as a basic human right. Adolescents with ADHD should not be denied the right to holistic healthcare.